Analisis Literasi Keuangan Syariah: Studi Kasus Pegadaian Syariah Di Kabupaten Bogor - Zaman, Ainun Qomaruz; Widana, Oka (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study is to examine Islamic financial literacy among Pegadaian Syariah employees in Bogor and highlight the important role of adequate knowledge in implementing Islamic financial principles.. The findings suggest that while employees generally possess a solid understanding of fundamental Islamic financial literacy concepts—such as definitions, principles, and Sharia-compliant products—challenges remain in practice. These challenges include insufficient training and limited access to informational resources. Moreover, awareness of the importance of Islamic financial literacy in enhancing service quality and customer satisfaction is still lacking. The study recommends improving training programs and providing more comprehensive informational resources to help employees deliver services that better align with Sharia principles. In conclusion, this research emphasizes the need to enhance both the understanding and application of Islamic financial literacy among employees to support the growth of Pegadaian Syariah and build greater public trust in Islamic financial products.